Gazprom: From rent distributor to tax collector? - James Henderson; Arild Moe (The Oxford Institute for Energy Studies, 2024)
The financial losses recorded by Gazprom in 2023 driven by collapsing gas export revenue point to a wider transition in the role of the company, which has been at the heart of Russia's energy economy since the Soviet period. In the pre-crisis period, Gazprom was able to subsidize gas supply to domestic consumers thanks to its monopoly on lucrative Russian gas exports. But the 2023 results point to a new set of trends, with liquids making up the bulk of revenue and the strategic importance of gas fading as the company works to establish new eastern markets to replace its lost European buyers. Furthermore, higher domestic gas prices are serving to feed additional revenue to the state budget in the form of tax, reducing the company's capital budget and squeezing its cost base. With Gazprom now becoming more of a de facto government revenue collector than a rent distributor, and with the company's much weaker financial position, highlighted by the deterioration in its balance sheet as well as its profit and loss account, this report asks what the outlook for the company is in terms of both internal financial reform or a potential breaking up of its business model in favour of domestic competitors like Rosneft and Novatek.
Keywords: 330; Capital; China; Exports; Gas; Gazprom; LNG; MET; Novatek; Profit; revenue; Rosneft; Russia; Subsidy; tax